Perancangan Sistem Informasi Penggajian Karyawan Pada PT. Labani Media Nusantara Berbasis Web Menggunakan Metode SDLC - Jafri, Dafa Umar; Ananda, M.Riski; Asriza, Muhammad Arif; Meliala, Soﬁan Sauri; Irwan (Universitas Sari Mutiara Indonesia Medan, 2024)
This study aims to analyze and design a payroll information system that can replace the payroll data processing process using Microsoft Excel at PT. Labani Media Nusantara. The payroll process using Excel is considered less efficient because it is prone to input errors, difficult to manage complex data, and takes a long time to process reports. The research methods used include needs analysis, web-based system design, and evaluation of the performance of the new system compared to the old method. The system developed has main features such as automatic salary calculation based on attendance data, management of allowances and deductions, and creation of real-time salary reports. The implementation results show that the designed payroll information system is able to reduce errors by up to 70%, increase data processing time efficiency by up to 50%, and provide easy access and transparency of payroll data. This system is expected to improve the quality of payroll management at PT. Labani Media Nusantara as a whole.